Children's cognitive role-taking and problem-solving abilities relation to selected socio-personal variables - Palcon, Hipolito P. 1947-
This study determined the developmental stages of the Filipino child's cognitive role-taking ability. Eighty subjects from kindergaten to Grade 6 were tested individually with the House Model Test and the Problem Type Model Test. It was concluded that the child's ability in role-taking and reasoning increases with age and is correlated with school performance for the high SES but not for the low SES.